Brand Equity dan Strategi Repositioning Lembaga Pendidikan Dasar Islam dalam Arena Kompetitif - Khoiruzzaim Kurniawan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the complexity of brand equity and formulate a managerial repositioning model for Madrasah Ibtidaiyah (MI) Darussalam Pikatan as a private Islamic primary education institution operating in the competitive education arena in the Blitar region. This study uses a mixed methods approach with a parallel convergent design, integrating qualitative data (in-depth interviews, observations, document studies, and focus group discussions) and quantitative data (parent perception surveys). The results of the study indicate that MI Darussalam Pikatan is in a position of being stuck in the middle, squeezed between MIN 14 Blitar, which has state-based legitimacy, and SDI Hasyim Asy’ari, which is strong in symbolic capital and religious community ties. Through perceptual mapping analysis and SWOT-TOWS synthesis, this study identified a managerial repositioning model that emphasizes building alternative legitimacy based on measurable performance and Islamic character education that is contextual, inclusive, and modern. This model positions brand equity not merely as a marketing tool, but as a strategic management framework that integrates signature programs, the enhancement of academic and character quality, evidence-based communication, and the strengthening of the parent community. The novelty of this research lies in the formulation of the repositioning of Islamic educational institutions, which shifts from reliance on structural or charismatic legitimacy to performance-based and contextually relevant legitimacy. Conceptually, these findings contribute to the development of Islamic education management by emphasizing that the competitiveness of madrasahs can be built through the integration of Islamic values with modern managerial strategies that are adaptive to the dynamics of the education market.